Genetic characterization of measles virus circulating in Iran, 2021–2023 - Alireza Esmaeiloghli Amiryli; Simin Abbasi; Faezeh Tarpoor; Azadeh Shadab; Azam Saboori; Nazanin-Zahra Shafiei Jandaghi; Vahid Salimi; Talat Mokhtari-Azad (BMC Infectious Diseases)
Abstract Background Measles, an ongoing public health concern, demands continuous molecular surveillance and virus characterization for elimination. Despite Iran achieving measles elimination status in 2019 through robust molecular testing and vaccination, the COVID-19 pandemic disrupted global vaccination efforts, leading to increased measles-related morbidity and mortality. This study aims to overview measles virus serological and molecular traits in Iran from 1st January 2021 to 30th April 2023. Methods Following World Health Organization and Center for Diseases and Control protocols, serological tests were performed on suspected cases and the nucleoprotein (N) gene of confirmed cases were subsequently amplified using molecular methods and were sequenced afterwards for measles genotyping. Phylogenetic analysis was performed with the obtained sequences. Results Analyzing 17,343 suspected cases from 1st January 2021 to 30th April 2023, 936, 177, and 164 samples were positive using ELISA, quantitative Reverse transcription PCR, and Reverse transcription PCR, respectively. The B3 genotype predominated, notably in Iran’s South East (41%), Central (28%), and South (13%) regions. Provinces bordering countries with measles outbreaks exhibited higher risk of virus importation. Genetic comparisons with measles sequences submitted to NCBI and MeaNS databases revealed direct importation and contact transmission. Conclusion Regular surveillance and genetic analysis are critical for understanding measles transmission and reacting to outbreaks. The COVID-19 pandemic yielded mixed effects on measles cases, enhancing hygiene measures while causing underreporting and vaccination gaps. Vigilance against measles resurgence is crucial, requiring cross-border transmission studies, improving cross-border surveillance and adaptable vaccination strategies.